Environmental politics in the European Union : Policy-making, implementation and patterns of multi-level governance. - Knill, Christoph (Issues in Environmental Politics S., 2007)
This book provides a comprehensive introduction to the development, making and implementation of European Union environmental politics and identifies the central areas and instruments of EU environmental policy. It analyses the factors influencing not only the formulation but also the implementation of environmental measures in the complex multi-level setting of the EU. On this basis, it takes a critical look at the EU?s effectiveness and problem-solving capacity in the environmental field. Designed as a textbook at undergraduate and graduate level, the book employs a clear and insightful anal.